In vivo breath‐hold 1H MRS simultaneous estimation of liver proton density fat fraction, and T1 and T2 of water and fat, with a multi‐TR, multi‐TE sequence. Issue 6 (25th June 2015) - Hamilton, Gavin; Middleton, Michael S.; Hooker, Jonathan C.; Haufe, William M.; Forbang, Nketi I.; Allison, Matthew A.; Loomba, Rohit; Sirlin, Claude B.
Abstract : Purpose: To examine the intra‐examination repeatability of proton density fat fraction (PDFF) and T 1 and T 2 of liver water and fat as estimated by a novel multi‐repetition time (TR)‐echo time (TE) 1 H magnetic resonance spectroscopy (MRS)‐stimulated echo acquisition mode (STEAM) sequence that acquires 32 spectra for a range of TRs and TEs in single breath‐hold. Materials and Methods: Sixty‐seven subjects undergoing liver MRI examinations at 3T had three multi‐TR‐TE sequences acquired consecutively in a single session. This sequence was designed to allow accurate estimation of T 1 and T 2 of both water and fat, as well as PDFF, in a single breath‐hold. A standard long‐TR, multi‐TE sequence was also acquired to allow comparison of estimated PDFF. Regression and interclass correlation (ICC) analyses were performed. Results: There was strong agreement between PDFF estimated by the multi‐TR‐TE and long‐TR, multi‐TE sequences (slope 0.997; intercept −0.03; R = 0.997). The multi‐TR‐TE sequence had high repeatability for estimating PDFF (ICC = 0.999), water T 2 (ICC = 0.920), water T 1 (ICC = 0.845), and fat T 2 (ICC = 0.760), and moderate repeatability for estimating fat T 1 (ICC = 0.556). Conclusion: A novel multi‐TR‐TE sequence can estimate PDFF and water and fat T 1 and T 2 in a single breath‐hold. Refinement may be needed to improve repeatability for fat T 1 estimation. J. MAGN. RESON. IMAGING 2015;42:1538–1543.